A construç\~ao social da informalidade e da semiformalidade no Brasil: Uma proposta para o debate - Mauro Oddo Nogueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The current paper starts from the premise that the dynamic of the construction of informality and semiformality in the Brazilian economy cannot be understood simply from facts of economical nature. To these must be added, as codetermining, factors of historical and cultural order. The central hypothesis of this study is that formal and informal economies articulate and complement each other, through semiformality, in a single economic space in which the "Brazilian way of doing things" (jeitinho brasileiro) acts as the instrument responsible for the updating of the elements of said spaces in relation to one another. Thus, informality is not, in the Brazilian case, a necessarily pernicious phenomenon that must be "eradicated" so that the country can reproduce the development trajectories of central nations. It is, on the contrary, a fact of national history and culture, an integral and indissoluble part of its economic order and whose "overcoming" will only be possible from its perfect comprehension, acceptance and, only then, from the conformation of an institutionality, of a regulating apparatus, that comes close to this informality, so that it can be integrated in the rule of law, as it is of the real world.
Keywords: E26; N80; L51; 330; informality; semiformality; economy and culture